Characterization of tongue dorsum microbiome in wine tasters. (January 2023) - Duarte-Coimbra, Sofia; Forcina, Giovanni; Pérez-Pardal, Lucía; Beja-Pereira, Albano
Graphical abstract: Highlights: Wine tasting has a washing effect as shown by the lower diversity displayed in samples collected after the tasting event. Sparkling wine tasting is associated with lower microbiome diversity. A higher frequency of Actinomyces bacteria on the tongue dorsum microbiome of wine tasters suggests their crucial role in taste sensibility. The amount of wine affects microbiome composition, which is less diverse in individuals processing more wine samples. Genus Gemella is less abundant in wine tasters with longer careers and is negatively correlated with career length, which points towards a potential inhibitory effect in wine taste perception. Abstract: Taste plays a paramount role in food and beverage choice, with recent studies pointing to a potential influence of the microorganisms from the tongue dorsum - particularly bacteria - on flavor perception. Thus, the association between tongue dorsum biofilm and taste is a fundamental prerequisite for a better understanding of the role played by these bacteria in wine tasting. To study this impact, we have analyzed the microbiomes from 58 samples of the tongue dorsum surface from professional wine tasters and 30 samples from non professional wine tasters. The microbiome of each sample was characterized through metagenome sequencing of the 16S rRNA gene for taxonomic discrimination of bacteria. A total of 497 taxa were identified in the tongue dorsum, and significant differences in diversity were observed between the wine taster and the control group. The comparison of bacterial diversity between samples collected before and after wine tasting along with the presence of new bacterial taxa indicates a direct effect of wine on the microbiome of frequent wine tasters, particularly in those tasting sparkling wines.